The role of high-performance systems in achieving the quality of work life - Assistant Lecturer. Mohammed Hammadi Jaber AL-bakhati (Zien Journals, 2023)
The aim of the research is to discover the role of high-performance systems in achieving the quality of work life, as the independent variable high-performance systems were measured with a set of dimensions represented by (skillsenhancing practices, motivation-enhancing practices, practices enhancing participation opportunities) and the dependent variable (b) employee development, participation. compensation, supervision. Work environment) . As a sample was chosen from one of the formations of the Petrogyna Iraq company, consisting of (80) workers and various functional specializations, and a number of programs and statistical methods were used, including the SPSS program, the EXCEL program, the Pearson correlation coefficient, and the Cronbach alpha coefficient. And the development of strategic plans is weak at the level of the company, as well as the development programs for employees did not rise to the required level, and there was no real environment for the quality of work life in the research sample company. As well as a set of recommendations, the most important of which is that the research sample company should focus on the concept of high-performance systems, which would improve and develop its skills and motivation towards better performance, as well as enable it to invest opportunities that are reflected in the reality of the company by achieving its goals.
Keywords: high performance systems; quality of life the job